Location of glomerular immune deposits, not codeposition of immunoglobulin G, influences definitive renal outcomes in immunoglobulin A nephropathy. Issue 7 (16th August 2017) - Alvarado, Anthony S; Andeen, Nicole K; Brodsky, Sergey; Hinton, Alice; Nadasdy, Tibor; Alpers, Charles E; Blosser, Christopher; Najafian, Behzad; Rovin, Brad H
ABSTRACT: Background: It has been suggested that the prognosis of immunoglobulin (IgA) nephropathy (IgAN) is adversely affected if there is codeposition of IgG in the glomeruli or if immune deposits are present in the glomerular capillary walls. We sought to understand how these variables affect clinical outcome. Methods: A total of 80 IgAN biopsies were retrospectively divided into groups: (i) IgA without IgG deposition versus IgA + IgG and (ii) immune deposits restricted to the mesangium versus mesangium and peripheral capillary walls (PCWs). The association of these groups with the composite primary outcome of renal replacement therapy, renal transplant, death or doubling of serum creatinine (SCr) concentration was determined. The change in estimated glomerular filtration rate (eGFR) was also assessed. Covariates examined were age, sex, race, SCr and proteinuria level at biopsy and at follow-up, duration of follow-up, treatment, Oxford score and presence of crescents. Results: IgG codeposition showed a trend toward endocapillary hypercellularity (P = 0.082); there were no other baseline differences between the IgA ( n = 55) and IgA + IgG ( n = 25) groups. At a median follow-up time of 29 months, the combined primary outcome was reached in 24 patients, 16 with IgA and 8 with IgA + IgG (P = 0.82). Patients with immune deposits in the PCWs ( n = 21) presented with higher baseline proteinuria than those with deposits limited to the mesangium ( n = 59; P = 0.025), were more likely to have crescents/segmental glomerular necrosis on biopsy (P = 0.047) and were more likely to reach the combined primary outcome (P = 0.026). Biopsies with crescents/segmental glomerular necrosis were associated with endocapillary hypercellularity (P < 0.001). Conclusions: In this multicenter IgAN cohort, IgG co-deposition and the location of glomerular immune deposits in the PCWs were both associated with greater histologic activity on renal biopsy, but only the location of glomerular immune deposits in the PCWs was associated with a significantly increased risk for end-stage renal disease, transplant, death and/or doubling of SCr.